FEATURES OF THE CONTENT OF CELLULAR MESSENGERS OF INFLAMMATION IN YEY INJURIES (REVIEW) - Евгения Алексеевна Созуракова; Елена Владимировна Громакина; Ольга Андреевна Канаева; Вадим Гельевич Мозес; Елена Владимировна Рудаева; Светлана Ивановна Елгина; Кира Борисовна Мозес; Наталья Степановна Черных; Елена Владимировна Золото (The Publishing House Medicine and Enlightenment, 2022)
Injuries to the organ of vision account for approximately 20% of ocular pathology. Cellular and humoral reactions aimed at maintaining homeostasis of the internal environment of the body, including the eyes, have individual constitutional features. The important regulators of the severity of these reactions are cytokines, which can stimulate and/or inhibit them. Studies of the regulation of inflammation through the system of interleukins synthesized by the cells of the cornea and iris or of extraocular origin for additional diagnostics of eye pathology have been repeatedly proposed. The main biological fluids for the study of cytokines were blood and tears. The pathogenetic study of cytokines in the lacrimal fluid is not always justified, since the change in their concentration in the lacrimal fluid does not reflect the processes occurring in the eye. The concentrations of cytokines in the moisture of the anterior chamber of the eye in humans were studied in single experiments. According to the literature data, the constitutional features of the production of certain cytokines can shift their balance, leading to the formation of pathology of the cornea and lens. Due to the unique physiological characteristics of the organ of vision and its immune privilege, the issue of eye injury and its therapy is a multidisciplinary one. The regulation of the inflammation phase with a decrease in the phenomena of secondary damage and optimization of regeneration is one of the tasks in eye injury.